Artificial Intelligence and Bias in Religious Auhtority - Hanik L. Tarwiyyah (SEULANGA SYSTEM PUBLISHER, 2025)
This research examines the complex interaction between Artificial Intelligence (AI) and religious authority. The main focus of the study is the significant risk of algorithmic bias, which emerges as AI becomes increasingly integrated into various aspects of life, including the religious sphere. The potential for bias in AI systems can affect the interpretation of doctrine, religious education, and even the legitimacy of spiritual leadership. This study uses a qualitative approach through document analysis and case studies to understand how AI, defined as the ability of computational systems to mimic human intelligence, can inadvertently reinforce religious prejudices and stereotypes. The results show that AI bias can manifest in various harmful forms. These forms include religious stereotypes, religious misinformation or